IDH1/2 mutations in WHO grade II astrocytomas associated with localization and seizure as the initial symptom - Stockhammer, Florian; Deimling, Andreas von (Seizure, 2012)
Introduction Seizures are the most common initial symptom in patients with low-grade glioma and their occurrence strongly depends on the tumor location. The majority of low-grade gliomas reveal mutations in the genes encoding isocitrate-dehydrogenase 1 (IDH1) or 2 (IDH2). These mutations are associated with metabolic changes that are potentially epileptogenic. We investigated the correlation between IDH1/2 mutations and tumor localization and seizure as the initial symptom. Materials and methods This retrospective study included patients with a diagnosis of WHO grade II astrocytoma and cortical infiltration and in whom initial symptoms were documented and biopsy tissue was available for IDH1/2 analysis. IDH1/2 mutation analysis was performed by direct sequencing or by immunohistochemistry with an antibody which detects mutated protein IDH1 R132H. Sequencing was carried out if immunohistochemistry was negative. IDH1/2 status was defined as mutated if either of these investigations were positive. Results Seventy-nine patients were included. IDH1 or IDH2 mutation was present in 63 (80%) patients who on average were younger than patients without IDH1/2 mutation (40 vs. 47 years, p=0.0331, t-test). IDH1/2 mutations were associated with frontal tumor location (p=0.0202). All 12 tumors in the insula revealed IDH1/2 mutations. Seizure as the initial symptom was recorded in 57 (72%) patients and was associated with IDH1 or IDH2 mutation by multivariate analysis (OR 22.563, p=0.0019). Conclusion In WHO grade II astrocytomas, IDH1/2 mutations mostly occur in tumors infiltrating the frontal lobe. Seizure as the initial symptom is associated with IDH1 or IDH2 mutation.
Gesehen am 20.04.2018